Survival Peace: The Irony of the Women's School Peace Action - Tacoh, Yuliana; Mambu, Joseph Ernest; Mardimin, Johanes; Suwartiningsih, Sri (GoAcademica Research & Publishing, 2025)
This article investigates the role of the Women’s School community in implementing peace initiatives in the outskirts of Lake Poso. These initiatives aimed to reduce tensions and prevent direct conflict between local communities and a natural-resource extraction company. The community played a dual role: engaging in negotiations with the company while simultaneously experiencing the negative impacts of its operations, including land dispossession and the submergence of traditional rice fields. The study examines these contradictions through the lenses of negative and positive peace and Feminist Security Studies (FSS), with particular attention to structural violence. Using a qualitative case-study approach, based on semi-structured interviews and participant observation, the research analyses women’s motivations, their moral dilemmas, and the broader impacts on surrounding communities. The findings reveal that the women’s community engaged in a form of “survival peace” in which community de-escalation efforts were contingent upon the company’s provision of stable employment for their children. The article underscores the importance of women’s peacemaking by drawing on FSS critiques of traditional, state-centered definitions of security. It further demonstrates how the women’s community redefined security by shifting it from a state-centered framework to the practice of “survival peace”, mobilizing their collective agency to secure short-term household economic stability through the company’s employment opportunities, despite the risks of long-term environmental degradation.